ANALYSIS OF LIMESTONE QUARRY SLOPE STABILITY, NIMBOKRANG DISTRICT, JAYAPURA REGENCY, PAPUA, INDONESIA - Marcell Fandy, Patrick; Hutagalung, Minar Julita; Tambing, Frans Simbol; Belly Sahetapy, George; Sanggamele, Herlina (CV. Utility Project Solution, 2024)
Slope stability analysis generally uses the concept of factor of safety (FoS) value using several whole rock parameters. The slope stability analysis method that will be used in this research is the slope stability analysis method in open pit mines based on rock mass classification with the Rock Mass Rating (RMR) system and the Geological Strength Index (GSI) system and analyses the potential for landslides that can occur on slopes at that location with kinematics and limit equilibrium methods so that the type of landslide can be determined based on the intensity of the geological structure on the slope of the CV. Inti Jaya open pit limestone mine, in Wahab Village, Nimbokrang District, Jayapura Regency. This research aims to provide information on the current condition of the slope whether it is by safety standards, make slope engineering improvements and redesign safe slopes if unstable slope conditions are found. Research on the stability of limestone slopes begins with the collection of field data and rock samples. Furthermore, sample testing was carried out to obtain physical and mechanical properties and weighting of rock masses, which were then analysed to obtain the characteristics and quality of rock masses that would be applied using the finite element method with Slide 6 from Rocscience to determine the Factor of Safety (FK) and the design of safe slope geometry. The RMR value for slope 1 is 62, slope 2 is 61, and slope 3 is 62. So it can be concluded that the rock is included in rock mass class 2 with good quality. Based on the analysis of potential avalanche types, the three slopes have non-arc avalanche types. From the analysis carried out using Rocscience Slide 6.0 software, the FoS value for slopes in original, dry, and saturated conditions is obtained, where on slope 1: FoS in original conditions is 0.935, FoS in dry conditions is 1.619, and FoS in saturated conditions is 0.671. Then slope 2: FoS in original condition is 0.896, FoS in dry condition is 1.457, and FoS in saturated condition is 0.806. Slope 3: FoS in original condition is 3.490, FoS in dry condition is 4.199, and FoS in saturated condition is 3.368. So it can be concluded that slopes 1 and 2 are unsafe or unstable in original and saturated conditions so that landslides can occur. In the analysis of the FoS value of the actual condition of the slopes in the field using the Hoek & Brown method, the FoS value of slope 1 is 0.387, the FoS value of slope 2 is 0.579, and the FoS value of slope 3 is 1.272, it can be seen that the actual condition of the slopes in the field is slopes 1 and 2 in an unsafe or unstable state. Improvements must be made to the slope geometry to maintain the stability of the slope to remain safe or stable. The recommended improvement is to create a new working level for slopes 1 and 2, with steep height and large rock porphyry.